REFORMS OF PRESCHOOL EDUCATION IN UZBEKISTAN (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
The recent reforms in preschool education in Uzbekistan have aimed to enhance the quality and accessibility of early childhood education in the country. These reforms include updates to the preschool curriculum to align with modern educational standards, improvements in teacher training programs to ensure educators are equipped with the necessary skills and knowledge, and significant investments in infrastructure development to create a more conducive learning environment for young children. The impact of these reforms on early childhood education in Uzbekistan is significant, as they have the potential to improve the overall quality of preschool education and contribute to the holistic development of children in their formative years. This topic provides valuable insights into the ongoing efforts to strengthen preschool education in Uzbekistan and its potential implications for the future of early childhood education in the country.